Nonlinear problems with lack of compactness - Molica Bisci, Giovanni 1975-; Pucci, Patrizia 1952- (De Gruyter series in nonlinear analysis and applications, 2021)
This authoritative book presents recent research results on nonlinear problems with lack of compactness. The topics covered include several nonlinear problems in the Euclidean setting as well as variational problems on manifolds. The combination of deep techniques in nonlinear analysis with applications to a variety of problems make this work an essential source of information for researchers and graduate students working in analysis and PDE's